Condition of periodontium in patients with fixed orthodontic appliances - Andjelić, Jasminka; Matijević, Snežana (Vojnosanitetski pregled, 2014)
Background/Aim. Orthodontic patients should be familiar with techniques of maintaining oral hygiene as well as with proper methods of checking maintenance of oral hygiene. The aim of this study was to determine a correlation between condition of periodontium and techniques of maintaining oral hygiene in patients treated with fixed orthodontic appliances. Methods. The research population included 100 patients, aged 15–25, treated by the orthodontist from 2005 to 2010. The maintenance of oral hygiene and the condition of periodontium was assessed using the following indices: plaque index, gingival index, bleeding index and oral hygiene index. The study was carried out using data obtained from the especially designed questionnaire as well as by objective examination of periodontal condition in accordance with the World Health Organization methodology, using adequate indicators and indices. Results. The results of the study show a significant correlation between condition of periodontium and oral hygiene in those with fixed orthodontic appliances. The use of interdental brushes and mouthwash liquid, as well as teeth brushing, were among the most significant predictors of healthy teeth and mouth. Conclusion. Teeth and mouth hygiene determined by frequency of teeth brushing, using of interdental brushes and mouthwash liquid are the basic preconditions for preservation and promotion of tooth and mouth health in patients with fixed orthodontic appliances.
Keywords: orthodontic appliances; periodontium; oral hygiene; dental plaque index; periodontal index; questionnaires